A CASE OF KOUNIS SYNDROME AFTER BEE STINGS - Varım, Ceyhun; Varım, Perihan; Vatan, Mehmet Bülent; yılmaz, sabiye; kılıç, harun (Medicinski časopis, 2015)
Bee sting may cause hypersensitivity reaction, may range from simple allergic reaction to life-threatening anaphylactic reaction changing. Cardiac involvement, although rare, but vary vasospazm from ST elevation MI. 61 years old man presenting with acute inferior myocardial infarction After bee sting was presented. He was taken to the catheterization laboratory for coronary angiography after loading aspirin and clopidogrel. Coronary angiogram showed that, after right ventricular branch of RCA was totally occluded which most likely was the cause of the patient’s anginal symptoms.After successful angioplasty of the right coronary artery ,he inters coronary care unit. Patient was discharged with medical teraphy. As in our case, to allergen agents such as bee stings may cause Kounis syndrome. The most important step in Kounis syndrome is suspicion emergency depertmant. Key Words: myocardial infarction, hypersensitivity, immediate